Technologies of care and the engineering imaginary: Two approaches to assistive device design for the Global South. - Sigounas, Vaia Y. (Medical Anthropology Quarterly, 2024)
Assistive devices serve as vectors for the ideals, judgments, and goals that their society of origin has towards people with disabilities. For some Ugandan inventors and prosthetists, familiarity with sociocultural norms and consistent feedback allow them to design prosthetic limbs as technologies of care that specifically meet the needs of Ugandans using these devices. In contrast, many biomedical engineers living in the United States rely on what I call the "engineering imaginary" to produce universalized forms of assistive technology intended for people living in an essentialized Global South. Drawing on research with engineers, prosthetists, and people living with limb loss in Uganda and the United States, I investigate the social and cultural aspects of prosthetic limb design and argue that there is a cross‐cultural mismatch about what a prosthetic device does and what kinds of limbs it should fit. This mismatch becomes inscribed in the prosthetic device itself.